Reflective Metasurface for Multi-Band Polarization Conversion for Satellite Applications in 6G Networks - Humayun Zubair Khan; Abdul Jabbar; Jalil Ur Rehman Kazim; Jamal Zafar; Masood Ur-Rehman; Muhammad Ali Imran; Qammer H. Abbasi (IEEE Open Journal of Antennas and Propagation)
This study introduces a reflective polarization converter based on metasurface, designed to offer both Linear-to-Linear polarization (LLP) and Linear-to-Circular polarization (LCP). The design comprises two periodically arranged split ring resonators with a slotted stripe that operate in the X, Ku, and K bands. The three discrete frequency bands demonstrate over 90% Polarization Conversion Rate for LLP for oblique incidence waves up to 45°. Additionally, the proposed converter achieves Left-Hand Circular Polarization (LHCP) in two sub-bands and Right-Hand Circular Polarization (RHCP) in two sub-bands for oblique incidence waves up to 45°. The metasurface design introduced in this study exhibits significant potential for satellite applications in 6G networks, owing to its versatile LLP and LCP conversion properties in the X, Ku, and K bands.